Avoiding the housewife stigma: Self-employment as a female career choice - Carl Magnus Bjuggren; Magnus Henrekson (Research Institute of Industrial Economics (IFN), 2018)
This paper investigates career choices of women who marry high-income men. We find that women married to men in the top of the income distribution are more likely to enter self-employment, which is also associated with a lower income. This can be interpreted as a career choice that produces a more flexible work schedule in return for lower income. In a Nordic welfare state where work is the norm for women, self-employment offers a way to avoid the stay-at-home stigma. It allows one to stay in the workforce while enjoying approval from society and being in control of one's work schedule and personal demands.
Keywords: J16; J12; J13; J22; L26; 330; Career choice; Entrepreneurship; Marriage; Self-employment; Women